A new monocyte epigenetic clock reveals nonlinear effects of alcohol consumption on biological aging in three independent cohorts (N = 2242). (17th March 2022) - Liang, Xiaoyu; Sinha, Rajita; Justice, Amy C.; Cohen, Mardge H.; Aouizerat, Bradley E.; Xu, Ke
Abstract: Background: Assessing the effect of alcohol consumption on biological age is essential for understanding alcohol use‐related comorbidities and mortality. Previously developed epigenetic clocks are mainly based on DNA methylation in heterogeneous cell types, which provide limited knowledge on the impacts of alcohol consumption at the individual cellular level. Evidence shows that monocytes play an important role in both alcohol‐induced pathophysiology and the aging process. In this study, we developed a novel monocyte‐based DNA methylation clock (MonoDNAmAge) to assess the impact of alcohol consumption on monocyte age. Methods: A machine learning method was applied to select a set of chronological age‐associated DNA methylation CpG sites from 1202 monocyte methylomes. Pearson correlation was tested between MonoDNAmAge and chronological age in three independent cohorts ( N total  = 2242). Using the MonoDNAmAge clock and four established clocks (i.e., HorvathDNAmAge, HannumDNAmAge, PhenoDNAmAge, GrimDNAmAge), we then evaluated the effect of alcohol consumption on epigenetic aging in the three cohorts [i.e., Yale Stress Center Community Study (YSCCS), Veteran Aging Cohort Study (VACS), Women's Interagency HIV Study (WIHS)] using linear and quadratic models. Results: The MonoDNAmAge, comprised of 186 CpG sites, was moderately to strongly correlated with chronological age in the three cohorts ( r  = 0.90, p  = 3.12E−181 in YSCCS; r  = 0.54, p  = 1.75E−96 in VACS; r  = 0.66, p  = 1.50E−60 in WIHS). More importantly, we found a nonlinear association between MonoDNAmAge and alcohol consumption ( p model  = 4.55E−08, p x 2  = 7.80E−08 in YSCCS; p model  = 1.85E−02, p x 2  = 3.46E−02 in VACS). Heavy alcohol consumption increased EAAMonoDNAmAge up to 1.60 years while light alcohol consumption decreased EAAMonoDNAmAge up to 2.66 years. These results were corroborated by the four established epigenetic clocks (i.e., HorvathDNAmAge, HannumDNAmAge, PhenoDNAmAge, GrimDNAmAge). Conclusions: The results suggest a nonlinear relationship between alcohol consumption and its effects on epigenetic age. Considering adverse effects of alcohol consumption on health, nonlinear effects of alcohol use should be interpreted with caution. The findings, for the first time, highlight the complex effects of alcohol consumption on biological aging. Abstract : Evidence shows that monocyte plays an important role in both alcohol‐induced pathophysiology and aging process. In this study, we developed a novel monocyte‐based DNA methylation clock to assess the impact of alcohol consumption on monocyte age. We found that alcohol use affects epigenetic aging in a nonlinear manner, with heavy consumption increasing and nonheavy use decreasing the epigenetic age. Our study expands previous knowledge and provides new insights into the effect of a spectrum of alcohol use on epigenetic aging.